The Economy of Indonesia: Driven by Physical or Human Capital? - Agusalim, Lestari; Anggraeni, Lukytawati; Pasaribu, Syamsul H. (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
This study aims to analyze whether economic growth in Indonesia is driven by physical or human capital using panel data analysis consisting of all provinces over the last nine years. The estimation results show that the Indonesian economy is more likely to be driven by physical than human capital. The formation of human capital that has a significant positive effect on economic growth is health. However, the education variable represented by the mean years schooling has no significant effect on economic growth when including the control variable in the research model. To improve the quality of education, the state requires the government to provide substantial educational spending. However, the budget has not been used optimally so that the expected achievements of graduates are not achieved. In addition, education spending has not met the criteria for quality spending. In contrast to education spending, an increase in health spending will increase economic growth by improving the quality of health and life expectancy. A healthier society will have a high level of productivity that impacts the regional and national economy.